SUSTAINABILITY IN THE FRAMEWORK OF PEDAGOGY CONTENT KNOWLEDGE FOR PROSPECTIVE TEACHER IN TEACHING THE MATERIALS OF FEMALE REPRODUCTIVE SYSTEM TO IMPROVE STUDENTS’ SCIENCE LITERACY - W H, Eny Hartadiyati; Rahmawati, Meilina (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This study aims to determine the effect of the sustainability concept in the framework of prospective teachers on female reproductive system materials to improve the ability of students' science literacy. The study used two classes which are selected randomly as an experimental class, in one of the local high school in Grobogan District. Biology teacher candidates integrate the three aspects of sustainability those are socio-cultural, economic, and environmental in PCK as seen in the CoRe document, learning tools and female reproductive system as learning's material. Students have to answer science literacy questions before and after learning session. Science literacy abilities use level 1 to level 3. The answer scores consist of three assessment criteria, namely